UMP vehicle entry & exit monitoring system (UMP VEEMS) - Muhammad Zulhelmi, Mohd Fauzi (2015)
Lately, the problem of stolen vehicles is frequently happened. This happens not because there is no direct supervision towards the vehicle, but the methods used are less efficient. Not only vehicles parked in public places are likely to be lost, but the vehicles in an area with security guards are also likely to be lost. For example, in government departments such as the office parking area, housing areas with guard posts and even in Universiti Malaysia Pahang itself. Student and staff of UMP need a safer place to park their vehicles. In UMP, the supervision at guard post is done manually where a few security guards will be stationed at each guard post to monitor the entry and exit of vehicles. The possibility of stolen vehicle is high because there is no identity inspection done to every vehicle’s owner that enter and exit UMP area. Anyone can drive a vehicle inside UMP area with a condition that the vehicle has UMP sticker on it. The criminal may have stolen the vehicle by disguising as student or staff of UMP. To overcome this problem, UMP Vehicle Entry and Exit Monitoring System will be develop. This system can increase the safety of vehicle in Universiti Malaysia Pahang, especially for cars. With the existence of this system, the security guards of UMP Security Department will easily obtain the traffic report on vehicle entry and exit from UMP. This system will be able to record the vehicle registration number and matric ID of the driver.